2004
DOI: 10.1021/jp0373696
|View full text |Cite
|
Sign up to set email alerts
|

Ion Emission from Water Ice Due to Energetic Particle Bombardment

Abstract: Ion emission from water ice due to energetic particle bombardment is investigated in a combined molecular dynamics and tof-SIMS experimental study. Specifically, emission of water clusters A ( (H 2 O) n , where A ( denotes positive alkali metal ions, Li + , Na + , K + , Cs + or negative halogen ions, F -, Cl -, I -, from frozen ice films is investigated. In the experiments, different concentrations of NaI and KI salts were dissolved in water before freezing. The influence of ion charge and concentration is inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 38 publications
1
30
0
Order By: Relevance
“…Thus, the creation of new ions and attachment of the new ions to the molecule is possible. Moreover, the same simulations (Ryan et al, 2007) as well as the study of pre‐formed ions by Wojciechowski et al (2004a,b) show that recombination of near‐by ions to form neutral species is very probable. In addition to the formation of parent (M + H) + ions the model should, therefore, predict all the water cluster distributions mentioned above.…”
Section: Ionizationmentioning
confidence: 72%
See 1 more Smart Citation
“…Thus, the creation of new ions and attachment of the new ions to the molecule is possible. Moreover, the same simulations (Ryan et al, 2007) as well as the study of pre‐formed ions by Wojciechowski et al (2004a,b) show that recombination of near‐by ions to form neutral species is very probable. In addition to the formation of parent (M + H) + ions the model should, therefore, predict all the water cluster distributions mentioned above.…”
Section: Ionizationmentioning
confidence: 72%
“…They find that free matrix ions are formed in both the desorption and ablation regime although as discussed above, they find that the analyte ions remain embedded in clusters composed of matrix molecules throughout the simulation time (several nanosecond). In the second study, Wojciechowski and co‐workers examined the emission of pre‐formed salt ions from a water matrix in SIMS in a joint computation and experimental study (Wojciechowski et al, 2004a,b) They found experimentally that for over four orders of magnitude of salt concentration the ion intensities are relatively constant and more cations are emitted than anions. Moreover, for 1 M solutions the bare ion (e.g., Na + or I − ) is the predominant species over hydrated ions.…”
Section: Ionizationmentioning
confidence: 99%
“…Donsig and Vickerman9 have reported a doubling or tripling of the (H 2 O) n H + yield compared with that of (H 2 O) italicn+ after exposure of an ice film to gaseous HCl. Frozen salt solutions under C 60+ bombardment show that the emission of cationic water clusters is more prevalent than that of anionic water clusters 18. It seems clear that the rise in (H 2 O)H + reflects higher emission yields of protons probably near the impact site as a consequence of higher concentrations of protons in the ice film.…”
Section: Resultsmentioning
confidence: 98%
“…Incorporated water plays an important role in determining the yield of negatively charged monatomic species. Water ice drastically reduced the SI yields of negative ions compared to positive monatomic ions in computational studies [ 59 , 60 ], and this may explain why the SI intensities were lower in the FH cells. The insignificant decrease in the OH - intensity was not surprising as it is a water fragment.…”
Section: Resultsmentioning
confidence: 99%